Animal-Based Metaphors as Being a Lingua-Cultural Way in the Field of Football Club Titles: Зооморфная метафора как лингвокультурологический способ в области прозвищ футбольных клубов (Journal of the College of Languages (JCL), 2019)
Metaphor is a linguistic phenomenon related to people's cultures. It is an integral part of cultural heritage. This paper tackles the use of animal-based metaphors in the field of football club titles so as to draw comparisons between those in Russian with their counterparts in Arabic. Names of animals are used to refer to some clubs and teams, where these names or titles reflect animal features such as strength, preying on victims; or animal figures are employed in the club symbols, or due to the similarity of the club shirt to the animal outer shapes in colours. For instance, "an-Nawaris", which means gulls in English, is used to refer to az-Zawraa club due to the identity in colours of both the outer colours of the birds and the club shirt, and to the way players celebrate their scoring goals. "Suqoor" also, which means hawks in English, refers to the Air Force club; it agrees with the symbol of club, since a hawk is sharp-sighted and is able prey on victims instantly. As for "thiaabul-sahree", which means in English desert wolves, is related to ar-Ramadi Club, and symbolizes the players to having the ability to prey on the other teams at home-playground, and to over well-established teams. As for "Usoodul-hAasimah", which means lions of the capital-city, it is associated with Baghdad Club. The team thereof has the characteristics of lions in respect to strength and bravery, along with well-done goal defense. Titles employing animal names are often used in Arab, African and European Countries, as well as in the media. They add to the beauty and understanding of the texts.Аннотация Метафора является одним из важнейших языковых феноменов, тесно связанных с культурой народов и ставших неотъемлемой частью наследия цивилизации. Данная статья посвящена употреблению Зооморфных метафор в системе прозвищ футбольных клубов, их употребление в обеих языках и сравнение этих прозвищ между русским и арабским языками. Сборные и футбольные команды называются в честь определенных животных, символизирующих силу, хищность или символизируют герб клуба и сходство цвета формы команды с внешностью животного, например, Чайки – это прозвище принадлежит к футбольному клубу «Аль-Завраа». Это название взялось в совпадении цвета игровой футболки команды и полёт этих птиц похож на празднование футболистов этого клуба после забитого гола. Соколы – это прозвище футбольного клуба «Аль-Куа Аль- Джавия», принадлежащий к военно-воздушной авиации. Название означает острое зрение сокола и быстро нападает на животных. Волки пустыни – Это прозвище футбольного клуба «эр-Рамади». Это название символизирует о том, что футболисты этого клуба хищные и они играют дома сильно и выиграют всех футбольных клубов также ведущих Ирака. Львы столицы – это прозвище принадлежит к футбольному клубу «Багдад ». Это команда носит название столицы Ирака – Багдад. Команда имеет характера льва и отличается это команда силой и храбрости и крепкой защитой.Зооморфные прозвища используются больше всего в арабских странах, и в Африке и в Европе и как метафора в СМИ. Зооморфные прозвища украсят речь и тексты и сделают образ более понятным.